2002
DOI: 10.1063/1.1469897
|View full text |Cite
|
Sign up to set email alerts
|

Interconnect failure due to cyclic loading

Abstract: The damage generated by AC currents at 100 Hz in interconnects has been studied and compared with mechanical fatigue damage in thin films. The nature of the damage under the two loading conditions is qualitatively similar, supporting the idea that the AC current damage comes from mechanical cycling due to temperature swings on the order of 100 K from Joule heating in the interconnects. In both cases, the damage forms as surface wrinkles within single grains grow in amplitude and extent with time. The possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The calibration device consisted of both a resistive heater and a fourpoint resistance sensor shown in Figure 2. The device was designed to maintain a constant sensor temperature between the sensor voltage taps as previous FEA work and observations have shown that line temperatures vary at the ends of some interconnect structures (Keller et al, 2002). The small resistive heater and sensor provided a calibration source of comparable size and power output to the structure of interest, which as previously discussed is important when using a Wollaston probe at high temperatures.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The calibration device consisted of both a resistive heater and a fourpoint resistance sensor shown in Figure 2. The device was designed to maintain a constant sensor temperature between the sensor voltage taps as previous FEA work and observations have shown that line temperatures vary at the ends of some interconnect structures (Keller et al, 2002). The small resistive heater and sensor provided a calibration source of comparable size and power output to the structure of interest, which as previously discussed is important when using a Wollaston probe at high temperatures.…”
Section: Methodsmentioning
confidence: 98%
“…Finite element analysis (FEA) (Keller et al, 2002) and observations of damage development during testing suggest that temperature in the lines is not uniform. The line resistivity method of temperature measurement does not capture local temperature variation, and hence, we seek local measurements of temperature as a function of position to better characterize the strain state induced during testing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies showed that the effect of temperature field on the fatigue properties of metal films could be attributed to the thermal expansion mismatch in the film and the substrate. 23,37 The thermal strain Δε T can be expressed as 23,38 Δε…”
Section: Multiphysics Fatigue Model Of the Flexible Metal Filmmentioning
confidence: 99%
“…The failure of copper through silicon vias due to the thermally induced mechanical stress has been presented in References [10,11]. Mechanical deformations in electric interconnects due to thermal expansion mismatch has been reported in References [12,13]. The effects of the thermally induced mechanical stresses on light emitting diodes, plastic ball grid arrays and field-programmable gate arrays are studied and discussed in References [14][15][16].Similar studies on the effect of thermally induced stress on different composite and cement-based materials have also been reported in literature.…”
mentioning
confidence: 99%